DEVELOPMENT OF IN SERVICE JOB TRANING TRAINING MODEL IN IMPROVING THE COMPETENCE OF POST PANDEMIC COMMUNITY EDUCATORS ASSISTED BY QUIZZIZ APPLICATION - Dinno Mulyono; Wasilatussa'adah Wasilatussa'adah; Rivaldo Rivaldo (Journal Of Educational Experts (JEE), 2022)
This research was motivated by various conditions related to the current handling of the COVID-19 pandemic. Especially with the aim of educational programs for the community related to the current situation. Given the importance of public education in dealing with this problem, increasing the understanding of educators regarding the revitalization of educational programs in the PKBM environment is very important, especially regarding its role in dealing with post-pandemic education programs by using the Quiziz application as a learning medium. The theoretical background in this study is ecoliteracy related to environmental education and resilience related to community resilience to the ongoing pandemic. The research method used is a survey method with the aim of understanding the condition of the community during the pandemic condition and a questionnaire to determine the impact of information and indirect guidance from government officials and community education institutions. The respondents selected were learning residents and community members in PKBM Geger Sunten, Suntenjaya Village, Lembang, West Bandung Regency.